A coupled diffusion-kinetics model for analysis of contact-area FRAP experiment. - Wu, J; Fang, Y; Zarnitsyna, V; Tolentino, T; Dustin, M; Zhu, C (2008)
Kinetic rates and binding affinity of receptor-ligand interactions are important determinants of cell adhesion. Measurements of these parameters in fluid phase using soluble molecules (i.e., three-dimensionial parameters) do not necessarily correlate with their counterparts measured when both binding partners are respectively anchored to two apposing surfaces (i.e., two-dimensional (2D) parameters). Moreover, 2D affinities measured by different methods can differ by orders of magnitude. Here we describe a coupled diffusion-reaction model for the fluorescence recovery after photobleaching experiment previously used to demonstrate the dynamics of adhesive bonds in the contact area. Applying the mathematical model to the contact area fluorescence recovery after photobleaching experiment enables in situ measurements of 2D kinetic rates of the adhesion molecules and their retarded diffusion in a stable contact area. The mathematical properties of the model are characterized in this article and its experimental validation will be presented in the companion article.